Aizanoi und Pergamon, Türkei: Ländliche Heiligtümer der Meter-Kybele im Umland von Aizanoi und Pergamon - Ateş, Güler (e-Forschungsberichte des DAI, 2023)
In 2012, two subsidiary sanctuaries of Meter-Kybele in the rural hinterland of Aizanoi and Pergamon were thoroughly examined. In both cases, terracotta figurines of Hellenistic-Roman times were found which resembled the goddess’s image of the main sanctuaries in Aizanoi and Pergamon. Therefore, the first part of the study deals with the central cave sanctuary of Meter- Kybele in Aizanoi and it rural branch at İlicikören. The second part focusses on the mountainous sanctuary at Mamurt Kale near Pergamon and a recently discovered rural sanctuary on Molla Mustafa Tepesi as a promising comparison.